Literalität in kinderund jugendliterarischen Werken - KUZMINYKH, KSENIA (Glottodidactica, 2019)
The article starts with a discussion of the essential theories of literature. It focuses on the historical development of books for children and young-adults. Worldwide there are three childhood myths, which are unfolded in successful children's books and which correspond to socially conditioned concepts of childhood. The Enlightenment childhood utopia sees children as promising for the future and improving human relationships. This idea explains the phenomenal resonance of books with educational and instructive concepts. In the 20th and 21st centuries this concept has become very popular again. By contrast, Romanticism developed another, second childhood myth, which combines not a future but a paradisiacal past with the image of childhood. In doing so, the holistic and naïve childlike world reference is stylized into an ideal that expresses the backward-looking yearning of adults. In addition to the Enlightenment and the Romantic childhood myths, there is a third, a negative view of childhood, which has also found expression in children's classics worldwide. This refers to the myth of the evil child, who is originally committed to the Christian doctrine of original sin. In the next step the article traces different modes of reading. These are the literary mode and documentary/pragmatic mode. Then, based on fragments taken from children’s and juvenile books from different periods, the article demonstrates the role of literacy in texts written for children and young adults, and the role of children and young-adult books for reading competence. While the paper examines these ideas within different novels though history, it also raises questions about the aesthetics and epistemic value of literature.